Optimal temperature range for determining magnetocaloric magnitudes from heat capacity. (9th November 2016) - Moreno-Ramírez, L M; Blázquez, J S; Law, J Y; Franco, V; Conde, A
Abstract: The determination of the magnetocaloric magnitudes (specific magnetic entropy change, Δ s M, and adiabatic temperature change, Δ T ad ) from heat capacity ( c H ) measurements requires measurements performed at very low temperatures ( 0 K) or data extrapolation when the low temperature range is unavailable. In this work we analyze the influence on the calculated Δ s M and Δ T ad of the usually employed linear extrapolation of c H from the initial measured temperature down to 0 K. Numerical simulations have been performed using the Brillouin equation of state, the Debye model and the Fermi electron statistics to reproduce the magnetic, lattice and electronic subsystems, respectively. It is demonstrated that it is not necessary to reach experimentally temperatures very close to 0 K due to the existence of certain starting temperatures of the experiments, the same for Δ s M and Δ T ad, that minimize the error of the results. A procedure is proposed to obtain the experimental magnitudes of Δ s M and Δ T ad with a minimum error from c H data limited in temperature. It has been successfully applied to a GdZn alloy and results are compared to those derived from magnetization measurements.